2022
DOI: 10.1177/09544054221100603
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different cutting edges caused by tool wear on cutting process of titanium alloy TC21 based on finite element model

Abstract: Titanium alloys have emerged as a significant aerospace material due to the high strength, good corrosion resistance and high temperature resistance thereof, but such alloys also have poor machinability because of the unique properties. Rapid tool wear is a serious problem for titanium alloy machining, with tool wear resulting in different tool edges. In the present study, finite element technology was used to establish a 2D cutting numerical model, so as to investigate the influence of the different cutting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This method provides support for the research on chip formation, cutting temperature prediction, microstructure evolution, cutting force and residual stress [21][22][23]. In addition, finite element technology has become an indispensable means to study the cutting mechanism of titanium alloys [24][25][26][27][28][29][30][31][32]. Davim et al [23] integrated many of the relevant aspects in the development of coolant assisted finite element method (FEM) simulations applied in difficult-to-cut materials, including titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…This method provides support for the research on chip formation, cutting temperature prediction, microstructure evolution, cutting force and residual stress [21][22][23]. In addition, finite element technology has become an indispensable means to study the cutting mechanism of titanium alloys [24][25][26][27][28][29][30][31][32]. Davim et al [23] integrated many of the relevant aspects in the development of coolant assisted finite element method (FEM) simulations applied in difficult-to-cut materials, including titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have been conducted to study the phenomenon of saw-toothed chip formation based on the FE analysis of cutting process. 2326 It has been found that the accuracy of these analyses is highly dependent on mesh parameters. In chip formation simulations, the influence of mesh parameters has been examined to decrease mesh dependence.…”
Section: Introductionmentioning
confidence: 99%